"Road to the Stars". Oxford XI; European Society for Astronomy in Culture (SEAC) 25; Inspiration of Astronomical Phenomena (INSAP) X Joint Conference, Santiago de Compostela 18th–22nd September 2017. (13th March 2018) - Boutsikas, Efrosyni
Abstract : "Road to the Stars". Oxford XI; European Society for Astronomy in Culture (SEAC) 25; Inspiration of Astronomical Phenomena (INSAP) X Joint Conference, Santiago de Compostela 18th–22nd September 2017